Book Review of "Permanent Record" by Edward Snowden - Jyotirmoy Banerjee (International Journal of Nuclear Security, 2020)
Sleeping through his school lectures and facing a broken home, this computer prodigy first joined the US army’s Special Forces. An accident while training broke his legs. The incident marked a volte face in Edward Snowden’s career.